Marine flooding hazard mapping on the Mostaganem coastal zone using an empirical approach and geospatial tools (Geo-Eco-Marina, 2024)
Significant global warming, particularly sea level rise, is expected to increase the intensity of marine flooding events on low-lying coastlines. Mostaganem Bay is one of the areas most significantly impacted by this phenomenon. The purpose of this study is to map the risk of marine flooding along the Mostaganem coast. It is based on empirical approach, considering several variables (wave surges, sea level rise and tide). All these variables are integrated within a Geographic Information System. Results show that 13% and 24% of the study area will be at risk of marine flooding, for minimum (8 m) and maximum (9.5 m) inundation levels, respectively. The most affected sectors are expected to be the port of Mostaganem, coastal tourism infrastructure and urban areas. Several adaptation options are proposed to reduce coastal vulnerability to marine flooding; however, these actions should be based on integrated Coastal Zone Management Plans (CZMP).
Keywords: sea level rise; marine flooding; coastal hazard; coastal vulnerability